Compliance of participants undergoing a '5-2' intermittent fasting diet and impact on body weight. (December 2022) - Cook, Florence; Langdon-Daly, Jasmin; Serpell, Lucy
Summary: Background: Intermittent fasting (IF) has grown in popularity as a weight loss tool, where caloric intake is fully/partially restricted on a recurring basis. This study aimed to assess compliance with IF fast-day calorie restriction and whether 5-2 IF leads to reduced overall energy intake, weight loss and compensatory increased energy intake on non-fast days. Method: Participants completed diet diaries at baseline and 28 days post 5-2 IF in a repeated measures within-subjects design. 5-2 IF required restricted energy intake to 500 kcal/day (women), 650 kcal/day (men) on two 'fast' days/week whilst eating ad-libitum on other days. Results: 52 participants were included (n = 42 female; age 44 ± 11.2yrs). Median weight loss after 28 days 5–2 IF was statistically significant (1.8 [-2 - 7.3 IQR = 2.2]kg; 2.8 [-2.7–11.2 IQR = 2.5]% p < 0.001). There was a significant reduction in total energy intake during 5–2 IF compared with pre-diet (median 1288.0 [IQR 423.8]kcal and median 1751.5 [IQR 505.3]kcal respectively, p < 0.001). Carbohydrate, protein and fat consumption proportionately reduced during 5–2 IF. Participants had significantly higher energy intake (p < 0.001) on non-fast days that followed a fast day (1928.4 ± 711.9 kcal) compared to non-fast days not following a fast day (1316.2 ± 310.0 kcal). 55.8% complied with fast day calorie restrictions. Conclusion: 5-2 IF was associated with significantly reduced energy intake, and weight loss over a 28-day period. Compliance rate was lower than most previous studies. Participants had significantly higher energy intake on non-fast days following fast days suggesting fasting may lead to over-compensation. Further research should investigate strategies to improve compliance and long-term sustainability of IF diets.